1991
DOI: 10.1056/nejm199109123251105
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Treatment Options for Alcohol-Abusing Workers

Abstract: Even for employed problem drinkers who are not abusing drugs and who have no serious medical problems, an initial referral to AA alone or a choice of programs, although less costly than inpatient care, involves more risk than compulsory inpatient treatment and should be accompanied by close monitoring for signs of incipient relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(110 citation statements)
references
References 18 publications
9
101
0
Order By: Relevance
“…Research suggests that AA itself can have an incremental effect when combined with formal treatment, and that AA participation alone may be as effective as formal treatment is (43)(44)(45).…”
Section: Treatment and Early Intervention Servicesmentioning
confidence: 99%
“…Research suggests that AA itself can have an incremental effect when combined with formal treatment, and that AA participation alone may be as effective as formal treatment is (43)(44)(45).…”
Section: Treatment and Early Intervention Servicesmentioning
confidence: 99%
“…Of these seven studies five favored inpatient programs, which proved to be the most intensive. Walsh et al [60] randomized patients to three treatment modalities: regular AA meetings, AA meetings with 2 weeks of prior hospitalization, and client's choice of treatment. They found that the group with 2 weeks prior hospitalization addressed drinking problems significantly better.…”
Section: Why Do Programs Differ In Effectiveness?mentioning
confidence: 99%
“…24,25 One exception to this is the study by Walsh et al, 26 which showed that among workers referred to an employee assistance program, those who were randomly assigned to a 3-week inpatient alcohol treatment program had significantly better alcohol-related outcomes than workers who were assigned to mandatory AA attendance only. Workers assigned to a third group were allowed to choose their treatment and had outcomes intermediate between the other two groups.…”
Section: Rehabilitationmentioning
confidence: 99%
“…The type of motivated, alcohol-dependent individual who persists with AA might do just as well with other forms of supportive therapy. In fact, the few randomassignment studies that have been conducted 26,[49][50][51] do not indicate that AA (or similar programs) is more effective than other types of treatment. Because of its widespread availability and the key role it plays in helping some alcohol-dependent individuals in their efforts at recovery, more systematic research directed at better understanding the process by which AA exerts its beneficial effects is needed, as are methods to enhance participation in 12-step programs.…”
Section: Treatment Of Alcohol Dependencementioning
confidence: 99%